Pendidikan Sastra: Pengetahuan Sastra di Sekolah Menengah Atas - Wijaya, Ana Merlin (Educationist: Journal of Educational and Cultural Studies, 2025)
Elaborating the problems of developing literary education in secondary schools is a real and urgent task, not only for achieving a high level of literary teaching in the 1990s and subsequent years, but also for the correct methodological orientation of research and for the practical direction of the modern school. Future perspectives in the development of the literary education system that have already been realized or are recorded in the present. Kudriashev (1976)